Synthesis of Potential Biologically Active 4,5-Dimethoxy-2-[3-oxo-3-phenylprop-1-en-1-yl]benzene Sulfonic Acid Derivatives - Shahid, Bilal; Zia-Ur-Rehman, Muhammad; Ahmed, Naveed; Athar Abbasi, Muhammad; Zaheer, Muhammad (Asian Journal of Chemistry, 2013)
A series of potential biologically active 4,5-dimethoxy-2-[3-oxo-3-phenylprop-1-en-1-yl]benzenesulfonamides was synthesized. 3,4-Dimethoxybenzaldehyde was condensed with acetophenone followed by its chlorosulfonation to get 4,5-dimethoxy-2-[3-oxo-3-phenylprop-1-en-1-yl]benzenesulfonyl chloride, which was further reacted with a number of amines and hydrazides to get the 4,5-dimethoxy-2-[3-oxo-3-phenylprop-1-en-1-yl]benzenesulfonic acid derivatives. All the synthesized compounds were subjected to preliminary evaluation for their antibacterial activity against selected strains of gram positive and gram negative bacteria. Some of the assayed compounds showed marked activity.